Bmal1 knockout aggravates Porphyromonas gingivalis-induced periodontitis by activating the NF-κB pathway - Ye TIAN; Xinran LIU; Qiuyu LU; Jiaxin LI; Tianqi WANG; Mei TIAN; Yan DING; Jinle LI (Journal of Applied Oral Science)
Abstract Circadian rhythm disorders and NF-κB are closely linked and can exacerbate periodontitis. However, the mechanisms via which circadian rhythm-related genes influence periodontitis are not yet fully understood. Objective We investigated the effect of brain and muscle Arnt-like protein-1 (BMAL1) on the NF-κB pathway and downstream inflammatory factors on periodontitis. In this study, Bmal1 homozygous knockout and periodontitis mouse models were established. Methodology Bone marrow-derived macrophages (BMDMs) from Bmal1-/- mice were cultured and stimulated with lipopolysaccharides. Bone resorption was detected using micro-computed tomography and histological analyses. Gene and cytokine expression was assessed using quantitative reverse-transcription PCR and ELISA. The nuclear translocation of p65 was detected using immunofluorescence. Results Our findings indicate that Bmal1 knockout exacerbates periodontitis severity in mice by activating the NF-κB signaling pathway with increased nuclear translocation of p65 (p<0.05), as well as increased expression of Il-1b, Il-6, and Tnfα (p<0.01), along with decreased Nr1d1 expression (p<0.05) in BMDMs under inflammation. Conclusion The results highlight the protective role of Bmal1 in periodontitis and suggest its potential link to the circadian clock's influence on the disease.